Econet for floodplain of Seim river (Sumy and Chernihiv regions, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Еconet project for floodplain of Seim river was developed, three key territories of local level (Piskivska, Konotopsko-Putyvlska, Baturynska) and Seimskyi regional ecocorridor were defined. Their characterization according to the method was completed. In the article the ways of integration for econet were proposed that were developed to the national ecological network due to favorable location of the region between Poliskyi, Galytsko-Slobozhanskyi, Dniprovskyi and Siversko-Donetskyi national level of ecological network. Connection ways of this econet with key territories of local level by local level ecological corridors were proposed.
Keywords: econet, floodplain of Seim river, conservation of biodiversity.